A new species of Camaridium (Orchidaceae: Maxillariinae) from the cloud forests of Colombia - Rodríguez Martínez, Lizeth; Blanco, Mario Alberto (Phytotaxa, 2015)
Camaridium perezianum is described from the remnant cloud forests of Valle del Cauca Department (western range of the Andes, southwestern Colombia). This new species is most similar to C. nutantiflorum, from which it differs by its subrhombic, apically rounded labellum and by its ligulate, minutely trifid, basally papillose callus. The seemingly bifid callus reported for C. nutantiflorum is shown to be an artifact caused by longitudinal splitting when flattening the labellum; the callus in living and liquid-preserved flowers is thick and widely obtuse. A key to the six species of the C. carinulatum alliance is provided.